The table that ran away to the woods - Themerson, Stefan; Themerson, Franciszka (London : Tate, 2012)
Tells the tale of a writing desk that one day 'grabbed two pairs of shoes/ran downstairs, and took flight', escaping into the countryside with its owners in barefoot pursuit.
Translated from the Polish.
boek
Keywords: Themerson, Franciszka; Children's stories